Sifat Mekanik Beton Serat Ijuk yang Terendam Air Laut - Chaeril Anwar; Erniati Bachtiar; Nur Khaerat Nur (Indonesian Journal of Fundamental Sciences, 2019)
This research aims to determine the value of mechanical properties in fiber fibers which are submerged in seawater and to find out the optimum length of fiber fibers to the mechanical properties of fiber fibers which are submerged in sea water. The method used is an experimental method carried out in the laboratory by varying the length of the fibers, which is 25 mm; 50 mm; 75 mm; and 100 mm with 4% fiber addition. Tests of mechanical properties carried out in the form of compressive strength, split tensile strength, and flexural strength. The results of the research challenge the palm fiber-concrete that the longer the fibers used in the concrete, the mechanical properties decrease. Fiber concrete submerged in seawater has higher mechanical properties than normal concrete. Optimum fiber length length in fiber concrete from the results of this study is 25 mm.